PENGARUH LABEL PERINGATAN KESEHATAN BERGAMBAR DAN TULISAN DI KEMASAN ROKOK TERHADAP INTENSITAS MEROKOK PADA SISWA SMP - Diana, Arvilla; Sabrian, Febriana; Karim, Darwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Adolescents have high curiosity and always want to try new things, which leads to the risk of smoking behavior. Several ways to overcome smoking behavior including the use of pictorial health warning labels about dangers of smoking. The aim of this research is to identify the effect of pictorial health warning labels on the packaging of tobacco with smoking intensity in adolescents. The design of this research was quasi experiment with non-equivalent control group. The research was conducted in SMPN 16 Pekanbaru with total sample of 34 respondents that were divided into 17 experimental group respondents and 17 control group respondents. The sampling technique used was proportionate stratified random sampling. Measuring instrument used was questionnaire sheets. The analysis used were univariate analysis and bivariate using dependent t test and independent t test analysis. The mean number of smoking intensity of experimental group before intervention was given 4,65 cigarettes and after intervention during 2 weeks the mean number decreased to 3,47 cigarettes. StatisticalÂ test results showed significant decrease in smoking intensity with p value (0,000 < Î± (0,05)), which means pictorial health warning labels on the packaging of tobacco had effect on smoking intensity in adolescents. It is expected that this approach can be an alternative to lessen the smoking behavior inÂ adolescents. Keywords: Adolescents, labels, smoking intensity.